Advance Directives and Outcomes of Surrogate Decision Making before Death - Silveira, Maria J; Kim, Scott Y.H; Langa, Kenneth M (The New England journal of medicine, 2010)
Data from a national study showed that more than one quarter of older adults who died between 2000 and 2006 required decision making at the end of life but lacked decision-making capacity. Most of these subjects had advance directives (living wills, health care proxies, or both) and received care consistent with their preferences. These findings suggest that advance directives are valuable. This national study showed that more than one quarter of older adults who died between 2000 and 2006 required decision making at the end of life but lacked decision-making capacity. Most of these subjects had advance directives and received care consistent with their preferences. Advance directives document patients' wishes with respect to life-sustaining treatment (in a living will), their choice of a surrogate decision maker (in a durable power of attorney for health care), or both. First sanctioned in 1976, advance directives were designed to protect patient autonomy 1 under the belief that patients who lose decision-making capacity are more likely to receive the care they want if they choose a surrogate decision maker, document their wishes in advance, or both. To promote the use of advance directives, Congress passed the Patient Self-Determination Act in 1990 2 mandating that all Medicare-certified institutions provide written information regarding . . .